2008
DOI: 10.1029/2008gl034374
|View full text |Cite
|
Sign up to set email alerts
|

First direct measurements of enthalpy flux in the hurricane boundary layer: The CBLAST results

Abstract: [1] Hurricanes extract energy from the warm ocean through enthalpy fluxes. As part of the Coupled Boundary Layer Air-Sea Transfer (CBLAST) experiment, flights were conducted to measure turbulent fluxes in the high-wind boundary layer of hurricanes. Here we present the first field observations of sensible heat and enthalpy flux for 10m wind speeds to 30 ms À1 . The analyses indicate no statistically significant dependence of these bulk exchange coefficients on wind speed. As a measure of hurricane development p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
156
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 162 publications
(181 citation statements)
references
References 22 publications
12
156
0
Order By: Relevance
“…On the other hand, the mesoscale downward sensible heat fluxes suggest that dry air is entrained downward from the flight level above. Zhang et al (2008) showed that the sensible heat fluxes tend to increase linearly with the decreasing height in the mixed layer. Although the buoyancy production or sink is much smaller than the shear production in the turbulent kinetic energy budget, which makes the boundary layer have a nearly neutral condition (Zhang et al, 2009), the subtle change of air-sea temperature difference correlates with the change of sign of the estimated surface sensible heat fluxes very well (Zhang et al, 2008).…”
Section: Spectra Of Potential Temperature and Cospectra Of Sensible Hmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, the mesoscale downward sensible heat fluxes suggest that dry air is entrained downward from the flight level above. Zhang et al (2008) showed that the sensible heat fluxes tend to increase linearly with the decreasing height in the mixed layer. Although the buoyancy production or sink is much smaller than the shear production in the turbulent kinetic energy budget, which makes the boundary layer have a nearly neutral condition (Zhang et al, 2009), the subtle change of air-sea temperature difference correlates with the change of sign of the estimated surface sensible heat fluxes very well (Zhang et al, 2008).…”
Section: Spectra Of Potential Temperature and Cospectra Of Sensible Hmentioning
confidence: 99%
“…Zhang et al (2008) showed that the sensible heat fluxes tend to increase linearly with the decreasing height in the mixed layer. Although the buoyancy production or sink is much smaller than the shear production in the turbulent kinetic energy budget, which makes the boundary layer have a nearly neutral condition (Zhang et al, 2009), the subtle change of air-sea temperature difference correlates with the change of sign of the estimated surface sensible heat fluxes very well (Zhang et al, 2008). The small values of the surface sensible heat fluxes used in the scaling method and their change of sign according to stability are probably the main reason why the surface scaling cannot be successfully applied to the cospectra of the sensible heat flux.…”
Section: Spectra Of Potential Temperature and Cospectra Of Sensible Hmentioning
confidence: 99%
See 2 more Smart Citations
“…To facilitate a proper comparison of the schemes in the four main calculations, the surface drag and heat and moisture exchange coefficients are modified to fit the results of the Coupled Boundary-Layer Air-Sea Transfer experiment (CBLAST: Black et al, 2007;Drennan et al, 2007;French et al, 2007;Zhang et al, 2008). The surface exchange coefficients for sensible heat and moisture are set to the same constant, 1.2×10 −3 .…”
Section: The Boundary-layer and Surface-layer Schemesmentioning
confidence: 99%